2022
DOI: 10.1101/2022.01.03.22268681
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reported Cases of Multisystem Inflammatory Syndrome in Children (MIS-C) Aged 12–20 Years in the United States Who Received COVID-19 Vaccine, December 2020 through August 2021

Abstract: BackgroundMultisystem inflammatory syndrome in children (MIS-C) is a hyperinflammatory condition associated with antecedent SARS-CoV-2 infection. In the United States, reporting of MIS-C after vaccination is required under COVID-19 vaccine emergency use authorizations. This case series describes persons aged 12–20 years with MIS-C following COVID-19 vaccination reported to passive surveillance systems or through clinician outreach to CDC.MethodsWe investigated potential cases of MIS-C after COVID-19 vaccinatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Yousaf et al recently reported 21 individuals ages 21 and younger with MIS-C following SARS-CoV-2 mRNA vaccination, 6 of whom had no prior evidence of COVID-19 infection. 23 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yousaf et al recently reported 21 individuals ages 21 and younger with MIS-C following SARS-CoV-2 mRNA vaccination, 6 of whom had no prior evidence of COVID-19 infection. 23 …”
Section: Discussionmentioning
confidence: 99%
“…This is greater than the original definition of MIS-C per CDC criteria, but it is within the range per WHO and the Brighton Collaborative Case Definition. 10 13 MIS-C cases with longer latency periods up to 16 weeks have been reported in the literature and it is possible that the original time frame of 4–6 weeks is too strict to encompass all cases of MIS-C. 23 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] The following researches show that there are many different reported MIS-C cases and results in kids (Table 2). [18,[20][21][22][23][24][25][26][27]…”
Section: Scarce Exacerbating Signs In Youngsters and Teenagers: Multi...mentioning
confidence: 99%
“…In children, MIS-V had a frequency of 1.5 cases per million of injected doses, with patients aged 12–20 years, presenting with fever, coagulopathy, mucocutaneous, cardiac, gastrointestinal, and renal involvement. They were treated with systemic CS and/or IGIV and had a favorable outcome ( 111 , 114 ). Similarly, adult MIS-V forms are also reported, with comparable course, treatment, and outcome ( 112 , 115 118 ) ( Supplementary Table 6 ).…”
Section: Anti-sars-cov-2 Vaccination-induced Cutaneous Vasculitismentioning
confidence: 99%